MiRNA Signatures of Insulin Resistance in Obesity. Issue 10 (21st August 2017) - Jones, Angela; Danielson, Kirsty M.; Benton, Miles C.; Ziegler, Olivia; Shah, Ravi; Stubbs, Richard S.; Das, Saumya; Macartney‐Coxson, Donia
Abstract : Objective: Extracellular microRNAs (miRNAs) represent functional biomarkers for obesity and related disorders; this study investigated plasma miRNAs in insulin resistance phenotypes in obesity. Methods: One hundred seventy‐five miRNAs were analyzed in females with obesity (insulin sensitivity, n  = 11; insulin resistance, n  = 19; type 2 diabetes, n  = 15) and without obesity ( n  = 12). Correlations between miRNA level and clinical parameters and levels of 15 miRNAs in a murine obesity model were investigated. Results: One hundred six miRNAs were significantly (adjusted P  ≤ 0.05) different between controls and at least one obesity phenotype, including miRNAs with the following attributes: previously reported roles in obesity and altered circulating levels (e.g., miR‐122, miR‐192); known roles in obesity but no reported changes in circulating levels (e.g., miR‐378a); and no current reported role in, or association with, obesity (e.g., miR‐28‐5p, miR‐374b, miR‐32). The miRNAs in the latter group were found to be associated with extracellular vesicles. Forty‐eight miRNAs showed significant correlations with clinical parameters; stepwise regression retained let‐7b, miR‐144‐5p, miR‐34a, and miR‐532‐5p in a model predictive of insulin resistance ( R 2  = 0.57, P  = 7.5 × 10 −8 ). Both miR‐378a and miR‐122 were perturbed in metabolically relevant tissues in a murine model of obesity. Conclusions: This study expands on the role of extracellular miRNAs in insulin‐resistant phenotypes of obesity and identifies candidate miRNAs not previously associated with obesity.